The effect of hindrance stressors on the emotional exhaustion among front-line healthcare workers in the recuperation period during the COVID-19 epidemic in China: a prospective cross-sectional study. Issue 6 (23rd June 2022) - Wang, Huan; Zhou, Xinyao; Song, Caiping; Yin, Pengpeng; Shi, Renzhong; Zhang, Hua; Dan, Yang; Wu, Hao; Ye, Junying
Abstract : Objectives: This study aimed to examine the influence and conditioning process of hindrance stressors on the emotional exhaustion of the front-line healthcare workers during recuperation, examine the potential mediating process of rumination, and explore the moderating role of organisational and family factors. Setting: This cross-sectional study was conducted during 12–20 July 2020. Total 418 questionnaires were collected from front-line healthcare workers by random cluster sampling. Hierarchical regression was performed to analyse the mediating effect of affective rumination using SPSS25.0, while PROCESS was used to further investigate the moderating role of servant leadership and family support. Participants: 418 healthcare workers were investigated randomly from front-line medical teams. Inclusion criteria included worked as front-line health workers and participated in the fight against COVID-19 in Hubei; age ≥18 years; normal cognitive and comprehension abilities under physical and mental health; volunteer to participate in this study. Exclusion criteria included recently affected by major events other than COVID-19 or those with a history of neurasthenia and trauma. Results: Using descriptive analysis of average value and SD measured by a five-item scale (MBI-GS), we found that front-line healthcare workers' emotional exhaustion score (2.45±0.88) was at the medium level. Hindrance stressors, mediated by affective rumination, had a significant positive predictive effect on emotional exhaustion. Servant leadership negatively moderated the direct effect of hindrance stressors on emotional exhaustion (β=−0.106, p<0.01). Family support positively moderated the impact of hindrance stressors on emotional exhaustion (β=0.082, p<0.05). Conclusions: During the recuperation period, after successfully controlling COVID-19 at the front line, the first-line healthcare workers should be screened through affective rumination evaluation to gain insight for targeted interventions. We find that servant leadership is beneficial in alleviating emotional exhaustion while family support worsens emotional exhaustion. We suggest that servant leadership should be further promoted in medical organisations, and family support should be applied correctly and cautiously.